A flat jacks method for in situ testing of brick masonry shear characteristics. (30th November 2020) - Armanasco, Alessandro; Foppoli, Dario
Highlights: Current methodologies to test masonry shear characteristics are highly destructive. A new method for shear tests has been calibrated in laboratory on real scale samples. The experimental results were compared with standard test methods. The new method was applied in situ to evaluate its operability and effectiveness. Further tests were performed to evaluate the effectiveness of strengthening methods. Abstract: The evaluation of the seismic behaviour of existing buildings is a problem increasingly felt in Italy, due to the many earthquakes that have recently occurred. The test methods currently used for the in situ assessment of the shear characteristics of masonry structures are highly destructive for the existing buildings, especially for heritage buildings. Furthermore, the way of preparation of the test panels causes damages that can affect the effective reliability of the results obtained from these methods. A new in situ testing technique named Flat Jacks – Shear Compression Test (FJ-SCT) Method has been developed by the authors based on the use of flat jacks to apply horizontal loads: this greatly reduces the impact of the test and therefore makes the testing technique applicable in a wide range of existing buildings. A calibration campaign was performed both in laboratory, using a specific testing frame, and in situ to evaluate the operability of the defined procedures. The analysis of the results and the proposal for the processing of shear strength data were then implemented. The technique proved to be reliable, the procedures to be efficient and effective and the results to be repeatable. Furthermore, specific tests were performed on buildings seriously damaged by the 2012 Emilia region earthquake to analyse the efficiency of masonry reinforcements. The shear tests were performed on original masonry panels and repeated on consolidated panels: the results proved the FJ-SCT method to be suitable to test the applicability of these reinforcement techniques and to estimate the strength improvement of the consolidated masonry.